2003
DOI: 10.1002/ange.200352737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Greatly Improved Reversible O2 Binding in a Structurally Modulated μ‐η22‐Peroxodicopper(II) Complex with Room‐Temperature Stability

Abstract: Die einfache O2‐Freisetzung aus einem Oxyhämocyanin‐Modellkomplex gelang erstmals mit dem neuen, bei Raumtemperatur stabilen μ‐η2:η2‐Peroxodikupferkomplex 1. Die Verlängerung der Cu‐O‐Bindungen, die durch die Brückenkopf‐Methylgruppen des Liganden hervorgerufen wird, ist die Ursache für die einfache O2‐Freisetzung. Die Bindung von CO und O2 durch 1 ist UV/Vis‐spektroskopischen Untersuchungen zufolge vollständig reversibel (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Furthermore, the coordination of the peroxido ligand O(3)O(4) in 3 is also remarkable.Crystallographically characterized precedents of this unusual m-h 2 :h 2 -O 2 coordination mode of the peroxido ligand to transition metals have only been reported for copper complexes that are models of oxyhemocyanin. [14] However, the related CuO 2 Cu moieties are systematically planar, [14] while the RhO 2 Rh framework has a butterfly conformation with a folding angle of 120.6(2)8. Moreover,[*] Dr.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the coordination of the peroxido ligand O(3)O(4) in 3 is also remarkable.Crystallographically characterized precedents of this unusual m-h 2 :h 2 -O 2 coordination mode of the peroxido ligand to transition metals have only been reported for copper complexes that are models of oxyhemocyanin. [14] However, the related CuO 2 Cu moieties are systematically planar, [14] while the RhO 2 Rh framework has a butterfly conformation with a folding angle of 120.6(2)8. Moreover,[*] Dr.…”
mentioning
confidence: 99%
“…Crystallographically characterized precedents of this unusual m-h 2 :h 2 -O 2 coordination mode of the peroxido ligand to transition metals have only been reported for copper complexes that are models of oxyhemocyanin. [14] However, the related CuO 2 Cu moieties are systematically planar, [14] while the RhO 2 Rh framework has a butterfly conformation with a folding angle of 120.6(2)8. Moreover, the O À O distance in the peroxido ligand (1.504 (4) ) is longer than that of the hydroperoxido ligand in 3 (1.450 (4) ) and that of 1 (1.463 (3) ) but similar to those of related mh 2 :h 2 -O 2 Cu complexes with hexapyridine dinucleating ligands (1.491(5), 1.485 (8) ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although oxyhemocyanin (oxyHc) and oxytyrosinase (oxyTy) have this species in the active site, they show different functions: oxygen transport and oxygen activation, respectively (Cooksey et al, 1997;Cuff et al, 1998;Holm et al, 1996;Solomon et al, 1992). Synthetic modeling approaches have greatly developed our understanding of the chemical characters of the Cu 2 (μ-η 2 :η 2 -O 2 ) species (Cahoy et al, 1999;Funahashi et al, 2008;Hu et al, 2001;Kitajima et al, 1992;Kitajima et al, 1989;Kodera et al, 2004;Kodera et al, 1999;Lam et al, 2000). Kitajima et al succeeded in synthesizing [(HB(3, 3 )Cu] 2 (O 2 ) (HB(3,5-iPr 2 -Pz) 3 = hydrotris{3,5-diisopropyl-pyrazolyl}borate (Trofimenko, 1999)) (1), which showed remarkable physicochemical similarities to oxyHc and oxyTy, and determining the crystal structures of the complex, which first characterized a Cu 2 (μ-η 2 :η 2 -O 2 ) structure for the active site of oxyHc, before the X-ray crystallographic studies of Hc were reported (Kitajima et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that lowtemperature oxygenation of [(iPr 3 TACD)Cu] 2 (CH 3 CN)]SbF 6 yielded a μ-η 2 :η 2 product with no trace of the bis(μ-oxo) isomer and concluded that the size of the ligand substituents and the ligand macrocycle ring size are key factors in controlling the relative stabilities of the μ-η 2 :η 2 -O 2 -peroxo and bis(μ-oxo) forms. Kodera et al reported the reversible dioxygen binding by the room-temperature-stable complex, [(L1)Cu] 2 (μ-η 2 :η 2 -O 2 ) (L1 = 1,2-bis[2-(1,1-bis(6-methyl-2-pyridyl)ethyl)-6-pyridyl]ethane) (3), and showed that the long Cu-O bonds and the strong O-O bond of 3 are favorable for easy release of O 2 since the O-O stretch of 3 is the strongest for Cu 2 (μ-η 2 :η 2 -O 2 ) complexes including oxyHc from the resonance Raman spectrum (Kodera et al, 2004). Masuda and his coworkers synthesized a new Cu 2 (μ-η 2 :η 2 -O 2 ) complex formed with α-isosparteine and benzoate (4) and determined the novel coordination structure of a carboxylate-bridged butterfly type μ-η 2 :η 2 -peroxide dicopper core (Funahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%